Penerapan Metode Cooperative Learning Tipe Make A Match untuk Meningkatkan Hasil Belajar Siswa di MI Miftahul Ulum Klapanunggal Bogor - Julianti Maulida; Agus Suryana; Indra Noviansyah (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2021)
This reserarch is a classroom action research through the maka a match model, which is carried out collaboratively whit two cycles. The main objective of this research is to improve the learning outcomes of scinse subjects in human digestive system material for fifth grade students through the make a match model with minimum completense criterian (KKM) 65. The subjects of this study were fifth grade student of MI Miftahul Ulum which consisting of 19 student, with a composition of 11 male and 8 female. The research was carried on the odd semester of academic year 2020/2021. The results showed that the percentage value of student completensess in cycle 1 obtained a value 58% and in cycle 2 obtained a value of 79%. Likewise with the results of observations of student behavior activities whit an averge value of 2,80 in cycle 1 and 3,70 in cycle 2. This study concludes that using the make a match model can improve scince learning outcomes in digestive apparaturs material in fifth grade humans of MI Miftahul Ulum Klapanunggal Bogor, beside this research is also able to increase student activity and learning process in class.